Corybas boholensis (Orchidaceae): A New Jewel Orchid Species from Bohol Island, Central Visayas, Philippines - Tandang, Danilo N.; Reyes, Tomas Jr.; Bustamante, Rene Alfred Anton; Callado, John Rey C.; Tadiosa, Edwin R.; Agoo, Esperanza Maribel; Lyon, Stephanie P. (Phytotaxa, 2020)
A new, critically endangered jewel orchid species, Corybas boholensis, is described and illustrated from forest over limestone on Bohol Island, Philippines. This diminutive species, belonging to the C. pictus complex, is distinct in having a deep red flower and a truncate, warty dorsal sepal with 9–11 veins at its widest point near the apex. This is the fifth species of Corybas recorded for the Philippines.